Immediate Amelioration of Severe Respiratory Distress in Sjögren's Syndrome with COVID-19 Treated with a Single Dose of Off-label Tocilizumab - Kataoka, Hiroshi; Kodama, Fumihiro; Tomita, Tomoko; Kondo, Makoto; Nagasaka, Atsushi; Nishikawa, Shuji; Mukai, Masaya (Internal Medicine, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has become an urgent global health issue. An older age and underlying conditions, such as diabetes, have been reported as risk factors, but whether or not autoimmune diseases increase the risk remains unknown. An 85-year-old man with Sjögren's syndrome developed a severe COVID-19 infection that required oxygen supplementation. After discussing the goals of care with him and his wife, off-label tocilizumab was given concomitantly, resulting in a rapid improvement in his symptoms and respiratory failure. This patient represents a supplementary case confirming the efficacy and safety of tocilizumab for COVID-19 in elderly patients with autoimmune diseases.